Percepção ambiental na proposição de indicadores para avaliação de impactos ambientais de parques eólicos - Andréia Castro de Paula Nunes; Gerda Lucia Pinheiro Camelo; Gesinaldo Candido Ataíde; Robson Garcia da Silva (Confins)
The preventive and mitigating potential of the environmental impact assessment has been limited due the absence of effective public participation and the use of indicators in this powerful instrument. Because of that, we searched to propose indicators for the evaluation of the environmental impacts of wind farms from the perception of the inhabitants of a settlement directly affected. To do so, we conducted a case study with semi-structured interviews, with residents of the settlement, and their information handled through Content Analysis. As results, fifteen indicators were proposed capable of monitoring and generating information about the environmental impacts of the wind farms most felt by the inhabitants of the settlement. Did we conclude that in the habitants perception, the means most affected by the impacts of wind farms are social and economic. In addition, we proved that environmental perception is capable of providing relevant information, generating inputs in decision-making applicable not only to wind farms, but also to other impactful activities.